IMPLEMENTASI KEBIJAKAN PENGEMBANGAN DAN PEMBERDAYAAN KOMUNIKASI SOSIAL DI DINAS KOMUNIKASI, INFORMATIKA DAN STATISTIK KOTA CIREBON - Nurudin Siraj; Agus Supriyadi; Nur Aulia Maulidina (Jurnal Governansi, 2019)
The research focuses on describing the implementation of the policy of developing and empowering social communication institutions of community information groups in Kejaksan Subdistrict, Cirebon City. In relation to the policy implementation, questions of the research are: (1) how the policy of community information groups in Kejaksan Subdistrict is implemented, (2) what factors support and inhibit the policy implementation in Kejaksan Subdistrict, and (3) what efforts are conducted to develop and to empower the social communication institutions of community information groups in Kejaksan Subdistrict. Method of the research is descriptive-qualitative. Data of the research are collected through observation and interviews. Results of the research indicate that the community information groups can be the facilitator for the community, the partner of the local government, the aspiration and information channel for the community. The implementation of the government policy of developing and empowering social communication institutions of community information groups in Kejaksan Subdistrict finds another dimension, namely the importance of budget and fund and monitoring, in addition to the factors of policy implementation used as an approach of the research.Keywords: Policy Implementation, Community Information Group, Social Communication, Empowerment.